INTEGRASI STOK BARANG PADA TOKO HANDPHONE DI PASAR SINGOSAREN SURAKARTA - Sukadi Sukadi (Universitas Islam Balitar Blitar, 2020)
This research is titled Integration of Stock Goods at a Mobile Store in Surakarta Singosaren Market. The final result of this research is an information system of goods integration in the mobile phone shop in Singosaren Market, Surakarta, which is expected to accelerate or help sellers get information on which stores are still in stock when there are buyers who want to buy goods and the seller happens to be empty. Then the sellers no longer need to ask directly to other sellers whether the stock is still there or not. The conclusion of this research is the integration of the stock information system at the mobile phone shop in Singosaren Market, Surakarta, if it can be implemented properly, will simplify and speed up shop owners in finding information on the availability of goods in other stores. It also has a function for processing purchase and sales transactions.